2023
DOI: 10.1186/s13020-023-00707-x
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective and neural circuit mechanisms of acupoint stimulation for cognitive impairment

Abstract: Cognitive impairment is a prevalent neurological disorder that burdens families and the healthcare system. Current conventional therapies for cognitive impairment, such as cholinesterase inhibitors and N-methyl-d-aspartate receptor antagonists, are unable to completely stop or reverse the progression of the disease. Also, these medicines may cause serious problems with the digestive system, cardiovascular system, and sleep. Clinically, stimulation of acupoints has the potential to ameliorate the common symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…For cognitive impairment, which is a frequently reported symptom caused by a variety of diseases with different phases, our review concentrated on neurodegenerative diseases, which share common pathogenesis and rehabilitation mechanisms to some degree. Previous review reported the mechanistic pathways of different interventions on acupoints, and summarized the molecular mechanisms of neuroprotective effects on cognitive deficits ( Zhang Z. et al, 2023 ). This study focused on acupuncture and electroacupuncture details, and highlighted the frequently studied acupoints and their targeted mechanistic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cognitive impairment, which is a frequently reported symptom caused by a variety of diseases with different phases, our review concentrated on neurodegenerative diseases, which share common pathogenesis and rehabilitation mechanisms to some degree. Previous review reported the mechanistic pathways of different interventions on acupoints, and summarized the molecular mechanisms of neuroprotective effects on cognitive deficits ( Zhang Z. et al, 2023 ). This study focused on acupuncture and electroacupuncture details, and highlighted the frequently studied acupoints and their targeted mechanistic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture provides an adjunctive approach to the rehabilitation of neurological disorders ( Shi, 2021 ; Lu et al, 2022 ; Zhang Z. et al, 2023 ). Clinical studies have validated the neurological functional improvement effect of acupuncture in cognitive impairment ( Yang et al, 2019 ) and movement disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In murine models for vascular dementia (VaD), it has been identified that EA could improve cognitive impairment by improving the proliferation of hippocampal neuro-stem cells (NSCs) to repair neurons and improve brain function ( Ahn et al, 2016 ). In addition, studies have indicated that acupoint stimulation has the potential to protect hippocampal neurons by preventing apoptosis, scavenging toxic proteins, and inhibiting the production of amyloid β-peptide and the phosphorylation of Tau protein ( Zhang et al, 2023 ).…”
Section: Can Acupuncture and Moxibustion Therapy Improves Cognitive I...mentioning
confidence: 99%
“…One of them is that stroke patients who undergo acupoint therapy will experience an increase in density from dendritic spines in the hypocampus region of the brain (Wang et al, 2020). In addition, acupoint therapy can increase the expression of cell division cycle 42, ras-related C3 botulinum toxin substrate 1, and F-actin proteins in the family of RhoGTPase, which function actively in the formation of cytoscoltonians from dendritic synaptics present in brain neurons (Zhang et al, 2023). Therefore, based on assumptions from the results of the study and the concept of theory and the results of previous research, it is concluded that this intervention is very effective in restoring motor function, especially swallowing disorders, in post-stroke patients with dysphagia.…”
Section: Effect Of Acupoint Therapy On Swallowing Function In Post-st...mentioning
confidence: 99%